Foot and ankle forklift injuries; diagnosis to treatment options, return to work and functional outcomes - BEKİROĞLU, GÜLNAZ NURAL; KOÇ, ERDEM; TOPKAR, OSMAN MERT; BAYSAL, ÖZGÜR (My University, 2023)
As our tertiary-level trauma center is close to an industrial zone and associated international port, industrial injuries are seen more often than is expected in routine practice. The aim of this study was to present the demographic data, treatment options, and changes in work-life of patients with foot and ankle injuries due to a forklift accident, and to determine the factors affecting the clinical outcome. The study was conducted in our university hospital and included patients who presented with a foot and ankle injury resulting from a forklift accident. Data were collected including age, sex, dominant extremity, history of trauma, presence of fracture, management (surgical or conservative), complications, time of return to work, workforce loss, and the American Orthopaedic Foot and Ankle Society (AOFAS) and Short Form Health Survey (SF-36) scores at the final follow-up examination. Evaluation was made of 132 patients, comprising 113 (85.6%) males and 19 (14.4%) females with a mean age of 32 years (range 16-65 years). The most frequently recorded occupational group was shipyard workers (50%). The most common mechanism of injury was crushing under the forklift wheel (n = 63, 47.7%). The most frequently injured foot region was the forefoot (47%). A total of 90 (68.1%) patients continued to work in the same position on return to work. The lowest mean AOFAS score (73.4) and SF-36 (physical component) score (37.3) were determined in cases with mixed region injuries (p = .0001, p = .0001). The wearing of protective footwear had no effect on the rate of return to work (p = .195), workforce loss (p = .34) and AOFAS score (p = .166). This study is the largest series of patients with foot and ankle injuries related to forklift accidents. Forklift injuries can be treated conservatively or surgically according to the clinical condition of the patient. The main indicators of return to work and functional outcome are which foot region is injured and whether or not the injury causes a fracture.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Ortopedi ve Travmatoloji; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Orthopedics and Traumatology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; ORTOPEDİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; ORTHOPEDICS; Cerrahi; Ortopedi ve Spor Hekimliği; Surgery; Orthopedics and Sports Medicine; 3; clinical outcome; foot and ankle; forklift injuries; workforce loss